2005
DOI: 10.1038/sj.gene.6364173
|View full text |Cite
|
Sign up to set email alerts
|

Immune response in silico (IRIS): immune-specific genes identified from a compendium of microarray expression data

Abstract: Immune cell-specific expression is one indication of the importance of a gene's role in the immune response. We have compiled a compendium of microarray expression data for virtually all human genes from six key immune cell types and their activated and differentiated states. Immune Response In Silico (IRIS) is a collection of genes that have been selected for specific expression in immune cells. The expression pattern of IRIS genes recapitulates the phylogeny of immune cells in terms of the lineages of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
356
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 359 publications
(361 citation statements)
references
References 77 publications
(45 reference statements)
4
356
0
Order By: Relevance
“…It is particularly interesting that CD127 expression has been reported to be threefold lower in effector/memory (CD45RO þ ) than naïve T cells (CD45RA þ ), 31 and greatly reduced in Th1 cells compared to resting memory cells. 22 As both CD45RO þ and Th1 cells are large sources of CD127 mRNA in PBMCs, a significant imbalance, with an excess of either or both, might be expected to contribute to the measured reduction in CD127 mRNA in PPMS detected in this study.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…It is particularly interesting that CD127 expression has been reported to be threefold lower in effector/memory (CD45RO þ ) than naïve T cells (CD45RA þ ), 31 and greatly reduced in Th1 cells compared to resting memory cells. 22 As both CD45RO þ and Th1 cells are large sources of CD127 mRNA in PBMCs, a significant imbalance, with an excess of either or both, might be expected to contribute to the measured reduction in CD127 mRNA in PPMS detected in this study.…”
Section: Discussionmentioning
confidence: 71%
“…As CD127 expression is very low in neutrophils, 22 and neutrophils account for the majority of mRNA in whole blood, we tested peripheral blood mononucleocytes (PBMC) RNA (that is, neutrophil depleted component), and found that CD127 mRNA expression was still much lower in PPMS (Pp0.003, Figure 2b). The majority of mRNA from PBMCs is from T cells (typically 80%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…49,53 The data illustrate the striking increase in linkage information that can be obtained by using appropriate SNP linkage panels. Recently, a number of reports have appeared using such panels, with evident success in identifying new regions of linkage.…”
Section: Discussionmentioning
confidence: 86%
“…To ensure that genes found significantly differentially expressed post-landing were not solely a consequence of increased proportion of NK cells, we used a multivariate linear model to regress individual gene expression levels against NK-cell specific marker genes. The criteria for classification as a NK-cell marker were that the genes must be these particular genes needed to be: 1) identified in multiple publications linking them to the NK-cell type; and 2) found intersecting across three independent cell type specific expression databases [CTen (Shoemaker et (Miller et al, 2013), we note that the model is fairly robust to choice of marker genes for cell type.…”
Section: Differential Gene Expression Analysismentioning
confidence: 99%